Epidural spinal involvement of Erdheim–Chester disease causing myelopathy. Issue 9 (September 2015) - Hwang, Brian Y.; Liu, Ann; Kern, Jason; Goodwin, C. Rory; Wolinsky, Jean Paul; Desai, Atman
Highlights Erdheim-Chester Disease (ECD) involvement of the spine is rare. ECD should be considered as a possible cause of myelopathy. Surgery can effectively and safely improve neurological symptoms in ECD patients.